Silat as the Source and Identity of the Minangkabau Ethnic Dance - Asriati, Afifah; Kosasih, Ahmad; Desfiarni, Desfiarni (Harmonia: Journal of Arts Research and Education, 2019)
This article is intended to get the concept of Minangkabau dance movement in the context of ethnic philosophical values. Today, ninik-mamak, cadiak pandai, and alim ulama in West Sumatra develop ideas about Minangkabau philosophy in all aspects of life. How this idea is reflected in dance movements? To answer this question, a qualitative method is used by taking six samples of popular Minangkabau traditional dance. The data were collected using Focus Group Discussion, observation, and interviews to confirm previous findings. Through the triangulation technique, it is expected to obtain credible data and be analyzed using the models of Miles and Haberman. The results of this study indicate that the basic movements of Minangkabau dance are silat movements. The martial arts movement is the basis of movement used by many traditional dances in Minangkabau. Every district has its unique cultural values and identities and these values are manifested in dance created by dance activists.